Developing enterprise sponsored virtual communities: The case of a SME's knowledge community - Simões, Dora
This paper presents a case in the development of a knowledge community support system in the context of an industrial association group in the construction sector. This system is a result of the Know-Construct project which aims at providing association sponsored SME communities of the construction sector with a sophisticated information management platform and community building tools for knowledge sharing. The paper begins by characterizing the so-called construction industry knowledge community. The Know-Construct system concept and the its general architecture are described, focusing on the semantic resources, in particular the ontologies structure. The final part of the paper depicts the approach to the actual introduction of the system in the community. An action-research approach was planned to obtain research results regarding the social acceptance of semantic resources such as the ontologies and technical classifications used in system.